Slicing the pie: how big could carbon dioxide removal be?. Issue 5 (28th July 2017) - Psarras, Peter; Krutka, Holly; Fajardy, Mathilde; Zhang, Zhiqu; Liguori, Simona; Dowell, Niall Mac; Wilcox, Jennifer
Abstract : The current global dependence on fossil fuels to meet energy needs continues to increase. If a 2°C warming by 2100 is to be prevented, it will become important to adopt strategies that not only avoid CO2 emissions but also allow for the direct removal of CO2 from the atmosphere, enabling the intervention of climate change. The primary direct removal methods discussed in this review include land management and mineral carbonation in addition to bioenergy and direct air capture with carbon capture and reliable storage. These methods are discussed in detail, and their potential for CO2 removal is assessed. The global upper bound for annual CO2 removal was estimated to be 12, 10, 6, and 5 GtCO2 /year for bioenergy with carbon capture and reliable storage (BECCS), direct air capture with reliable storage (DACS), land management, and mineral carbonation, respectively—giving a cumulative value of ~35 GtCO2 /year. However, in the case of DACS, global data on the overlap of low‐emission energy sources and reliable CO2 storage opportunities—set as a qualification for DAC viability—were unavailable, and the potential upper bound estimate is thus considered conservative. The upper bounds on the costs associated with the direct CO2 removal methods varied from approximately $100/tCO2 (land management, BECCS, and mineral carbonation) to $1000/tCO2 for DACS (again, these are the upper bounds for costs). In this review, these direct CO2 removal technologies are found to be technically viable and are potentially important options in preventing 2°C warming by 2100. WIREs Energy Environ 2017, 6:e253. doi: 10.1002/wene.253 This article is categorized under: Bioenergy > Climate and Environment Energy and Climate > Climate and Environment Energy and Development > Climate and Environment Abstract : Carbon dioxide removal methods for the intervention of climate change are discussed in addition to their potential annual impacts on a global scale. Relative CO2 removal potential per year (left) and projected cost of removal (right). Although DACS and mineral carbonation have the potential for high impact, based on the lower projected costs of BECCS and land management, these methods may be more appropriate initially.